DEVELOPMENT OF THE ENRICHMENT BOOK HIGH VALUE OF HUMANIS CONSERVATION IN WRITING TEXT DRAMA JUNIOR HIGH SCHOOL (PENGEMBANGAN BUKU PENGAYAAN BERMUATAN NILAI KONSERVASI HUMANIS DALAM MENULIS TEKS DRAMA SMP) - Sari, Ira Kartika (Universitas PGRI Sumatera Barat, 2018)
ABSTRAKTujuan penelitian ini adalah mendeskripsikan karakteristik kebutuhan buku pengayaan menulis teks drama, mendeskripsikan pengembangan buku pengayaan, mendeskripsikan penilaian ahli terhadap buku pengayaan. Penelitian ini menggunakan desain Research and Development (R&D) dengan lima tahapan penelitian. Prototipe dari buku pengayaan menulis teks drama adalah sampul buku, bagian awal buku (halaman judul, halaman hak cipta, pengantar, daftar isi, halaman persembahan, petunjuk penggunaan buku), bagian isi buku (contoh teks drama, materi, contoh menulis teks drama, rangkuman), dan bagian akhir buku (glosarium, profil penulis, profil ilustrator, daftar pustaka). Hasil penelitian yang berupa produk buku pengayaan bermuatan nilai konservasi humanis dalam pembelajaran menulis teks drama satu babak dapat digunakan sebagai buku pendamping buku teks. Kata kunci: buku pengayaan, menulis, teks drama, nilai konservasi humanis. ABSTRACTThe objective of this study was to describe the characteristics of the need for the enrichment book in writing drama texts, to describe the development of the enrichment book, and describe the experts’ evaluation towards the enrichment book. This research used Research and Development (R&D) design with five research stages. The prototype of the enrichment book is the book cover, the beginning of the book (title page, copyright page, table of contents, dedication page, instructions on the book usage), the book content (examples of drama texts, materials, examples of writing drama texts, summary), and the final part of the book (glossary, author profile, illustrator profile, bibliography). The result of this study in the form of enrichment book high value of humanis conservation in learning writing text drama one roof can be used as a supporting book for the textbook. Keywords: enrichment book, writing, drama texts, values of humanist conservation